Tunguska explosion and the Earth's magnetic field - Kovalyov, M.; Kovalyov, N.; Kovalyov, S. (Геофизический журнал, 2019)
For at least a century, the geophysicists have been wondering about the future of the Earth's magnetic field and whether it is going to flip, while the astrophysicists have been wondering what kind of celestial body exploded on June 30, 1908 by the river of Podkamennaya Tunguska. Using the data recently made available by NOAA, we demonstrate an intimate relationship between the two, previously thought completely unrelated, phenomena.